การพัฒนาตัวบ่งชี้ความสามารถพิเศษของนักกีฬาโปโลน้ำระดับเยาวชน - ธานินทร์ บุญญาลงกรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this study were (1) to develop the indicators of talented water polo players in youth level (2) to test the efficiency of the test ; and (3) to present the model of support and develop the U – 18 Thailand National Water Polo Team by using test of talented indicators of water polo in youth level. They were 4 stages of research procedure as follows: (1) to study the documents for evaluating the indicators talented of water polo player; (2) to construct the research instruments; (3) to study the quality of research instrument and (4) to present the model of support and develop the U – 18 Thailand National Water Polo Team.The research was found that the talented indicators of water polo in youth level were consisted of 5 indicators as follow: (1) the anthropometry indicators had 10 test lists, (2) the motor skill indicators had 7 test lists, (3) the psychology indicators had 4 test lists, (4) the physiology indicators had 4 test lists, and (5) the game intelligence indicators had 5 test lists. It was found that the content validity was at 0.76 (IOC). The construct validity was statistically significant at .05 in all items except the anthropometry talented identification test. The reliability of the test was also significant at .05 in all items and the reliability was at 0.91.The results of this research concluded that: the test which was used for evaluating the talented indicators of water polo players in youth level in 5 components as follow: (1) the anthropometry indicators (2) the motor skill indicators (3) the psychology indicators (4) the physiology indicators and (5) the game intelligence indicators had a quality in content validity, construct validity, reliability and also the test manual with details was also constructed to test and to select the talented water polo players in youth level.